Acute supra-therapeutic oral terbutaline administration has no ergogenic effect in non-asthmatic athletes - Sanchez, Anthony M. J.; Borrani, Fabio; Le Fur, Marie Amélie; Le Mieux, Anais; Lecoultre, Virgile; Py, Guillaume; Gernigon, Christophe; Collomp, Katia; Candau, Robin (European journal of applied physiology, 2013)
This study aimed to investigate the effects on a possible improvement in aerobic and anaerobic performance of oral terbutaline (TER) at a supra-therapeutic dose in 7 healthy competitive male athletes. On day 1, ventilatory threshold, maximum oxygen uptake and corresponding power output were measured and used to determine the exercise load on days 2 and 3. On days 2 and 3, 8 mg of TER or placebo were orally administered in a double-blind process to athletes who rested for 3 h, and then performed a battery of tests including a force–velocity exercise test, running sprint and a maximal endurance cycling test at Δ50 % (50 % between VT and ). Lactatemia, anaerobic parameters and endurance performance ( and time until exhaustion) were raised during the corresponding tests. We found that TER administration did not improve any of the parameters of aerobic performance ( p > 0.05). In addition, no change in kinetic parameters was found with TER compared to placebo ( p > 0.05). Moreover, no enhancement of the force–velocity relationship was observed during sprint exercises after TER intake ( p > 0.05) and, on the contrary, maximal strength decreased significantly after TER intake ( p < 0.05) but maximal power remained unchanged ( p > 0.05). In conclusion, oral acute administration of TER at a supra-therapeutic dose seems to be without any relevant ergogenic effect on anaerobic and aerobic performances in healthy athletes. However, all participants experienced adverse side effects such as tremors.